Assessment and Comparison of Total Salivary Protein and Salivary Flow Rate among Type I, Type II Diabetics and Healthy Controls - B.Niveditha; M. Kavitha; Mutum Sangeeta Devi; J. Manju; C.K. Vishnu Priya; D.K.S.Lakshminrusimhan (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: Diabetes mellitus characterized by either absolute insulin deficiency (Type I) or targettissue resistance (Type II) is associated with oral complications like xerostomia, gingivitis, periodontitis,odontogenic abcesses and soft tissue lesions of the oral mucosa. Saliva is a unique biological fluid and is alsoa characteristic biomarkers for different diseases.Several classes of drugs are found to be associated withdry mouth or salivary gland dysfunction or hypofunction, which in turn influences concentration of salivaryproteins. This leads to changes of oral health status among individuals using these drugs. Aim of the Study:To evaluate and compare the total salivary protein and salivary flow rate among Type I Diabetics, Type IIDiabetics and healthy controls. Materials and Methods: A total of 60 individuals have participated in thestudy which include 20 with Type I diabetes, 20 with Type II diabetes and 20 healthy controls. The study wasprospective in nature. Patients were asked not to eat or drink 2 hours before the time of saliva collection. Thesamples were collected in the same time of the day to avoid circadian variations. unstimulated saliva wascollected using spit technique. Patient was instructed to spit the saliva in graduated containers for a periodof two minutes. The flow rates were determined visually from graduated salivary containers as ml/min.After measuring the saliva volume the saliva sample was stored in deep freeze until protein estimation. Thetotal salivary protein in each salivary sample was determined using BioRad Protein Assay Dye Concentratemethod using BSA standard. Results: On comparing the total salivary protein among Type I, Type IIDiabetics and healthy controls, a significant difference in total salivary protein was found among Type IDiabetics and healthy controls and also among Type I and Type II Diabetics and there was a insignificantdifference in Type II Diabetics and controls. There was an insignificant difference in total salivary flowrate among Type I and Type II Diabetics and healthy controls. Conclusion: A significant difference in totalsalivary protein level among the diabetic and non diabetics emphasized that protein utilization by otherbiochemical metabolic pathways has an overall systemic response to glucose intolerance .With regards tosalivary flow rate ,the inconsistent results obtained may be due to the duration of diabetes, age range ofpatients and metabolic control of patients, class of drugs taken by the patient .